A Mononuclear Uranium(IV) Single‐Molecule Magnet with an Azobenzene Radical Ligand. Issue 49 (5th November 2015) - Antunes, Maria A.; Coutinho, Joana T.; Santos, Isabel C.; Marçalo, Joaquim; Almeida, Manuel; Baldoví, José J.; Pereira, Laura C. J.; Gaita‐Ariño, Alejandro; Coronado, Eugenio
Abstract: A tetravalent uranium compound with a radical azobenzene ligand, namely, [{(SiMe2 NPh)3 ‐tacn}U IV (η 2 ‐N2 Ph2 . )] (2 ), was obtained by one‐electron reduction of azobenzene by the trivalent uranium compound [U III {(SiMe2 NPh)3 ‐tacn}] (1 ). Compound2 was characterized by single‐crystal X‐ray diffraction and 1 H NMR, IR, and UV/Vis/NIR spectroscopy. The magnetic properties of2 and precursor1 were studied by static magnetization and ac susceptibility measurements, which for the former revealed single‐molecule magnet behaviour for the first time in a mononuclear U IV compound, whereas trivalent uranium compound1 does not exhibit slow relaxation of the magnetization at low temperatures. A first approximation to the magnetic behaviour of these compounds was attempted by combining an effective electrostatic model with a phenomenological approach using the full single‐ion Hamiltonian. Abstract : Uranium magnet : The mononuclear U IV complex with an azobenzene radical ligand [{(SiMe2 NPh)3 ‐tacn}U IV (η 2 ‐N2 Ph2 )] exhibits slow relaxation of magnetization with an energy barrier of 17.6 K. This unprecedented behaviour among U IV complexes, due to the interaction of the metal ion with the paramagnetic ligand, was investigated by means of an effective electrostatic model and provides a new strategy to design single‐ion magnets with non‐Kramers ions (see figure).